Establishing dose bands for commonly prescribed oral medications for children in the UK: Results of a Delphi study. Issue 7 (11th January 2021) - Rashed, Asia N.; Tomlin, Stephen
Abstract : Objective: To establish weight‐based dose bands for commonly used oral medicines, given in liquid forms, for children in the UK that could be used for prescribing and administering accurate and safe drug doses. Methods: A list of commonly prescribed, oral liquid medications was established from the medication dispensing database of four UK hospitals and a primary care database. The evidence base of currently used dose regimens for each drug was identified from paediatric reference books, summary of product characteristics and the literature. Then, weight‐based dose bands were developed and a modified Delphi process was used to achieve healthcare professional consensus about the suggested dose bands for each drug. Results: Forty‐six experts in paediatric medicines participated in the Delphi process (mean years of experience 17.3 ± 9.4 [standard deviation]) and assessed 45 oral liquid drugs in total. Four categories of weight‐based dose bands were established: drugs with two dose bands (17.8%, 8/45), drugs with three dose bands (64.4%, 29/45), drugs with four dose bands (15.6%, 7/45) and drugs with five dose bands (2.2%, 1/45). The 46 participants reached consensus on all the suggested dose bands for 53.3% (24/45) of the drugs. Consensus was reached in the first round of the Delphi process for 91.7% (22/24) of the drugs and after two rounds for two drugs. No agreement was achieved on any of the suggested dose bands for 26.7% (12/45) of the drugs. Conclusion: This study provides healthcare professionals with a set of recommended weight‐based dose bands for commonly prescribed oral liquid drugs for children. These bands could establish the basis for change in clinical practice to reduce dosing errors and improve healthcare for children.